Anti-neuroinflammatory effects of Ephedra sinica Stapf extract-capped gold nanoparticles in microglia - Park SY (Dove Medical Press, 2019)
Sun Young Park,1 Eun Hye Yi,2 Yoon Kim,2 Geuntae Park31Bio-IT Fusion Technology Research Institute, Pusan National University, Busan, Republic of Korea; 2HYUNDAI ENTEC Research Institute, HYUNDAI ENTEC, Busan, 46048, Republic of Korea; 3Department of Nanofusion Technology, Graduate School, Pusan National University, Busan, Republic of KoreaBackground: Combination therapy remains a promising strategy for treating neurodegenerative diseases, although green synthesis of gold nanoparticles for treating chronic neuroinflammation and studying their efficacy in treating neuroinflammation-mediated neurodegenerative diseases is not well assessed.Results: Here, Ephedra sinica Stapf (ES) extract was used as the reducing, capping, and stabilizing agent for gold nanoparticle synthesis. We developed ES extract-capped gold nanoparticles (ES-GNs) and investigated their anti-neuroinflammatory properties in microglia. ES-GNs displayed maximum absorption at 538 nm in ultraviolet-visible spectroscopy. Dynamic light scattering assessment revealed that ES-GN diameter was 57.6±3.07 nm, with zeta potential value of −24.6±0.84 mV. High resolution–transmission electron microscopy confirmed the spherical shape and average diameter (35.04±4.02 nm) of ES-GNs. Crystalline structure of ES-GNs in optimal conditions was determined by X-ray powder diffraction, and elemental gold presence was confirmed by energy-dispersive X-ray spectroscopy. Fourier transform-infrared spectroscopy confirmed gold nanoparticle synthesis using ES. Anti-neuroinflammatory properties of ES-GNs on production of pro-inflammatory mediators (nitric oxide, prostaglandin E2, and reactive oxygen species) and cytokines (tumor necrosis factor-α, IL-1β, and IL-6) in lipopolysaccharide (LPS)-stimulated microglia were investigated by ELISA and flow cytometry. ES-GNs significantly attenuated LPS-induced production of pro-inflammatory mediators and cytokines, which was related to suppressed transcription and translation of inducible nitric oxide synthase and cyclooxygenase-2, determined by RT-PCR and western blotting. ES-GNs downregulated upstream signaling pathways (IκB kinase-α/β, nuclear factor-κB, Janus-activated kinase /signal transducers and activators of transcription, mitogen-activated protein kinase , and phospholipase D) of pro-inflammatory mediators and cytokines in LPS-stimulated microglia. Anti-neuroinflammatory properties of ES-GNs were mediated by ES-GNs-induced AMP-activated protein kinase)-mediated nuclear erythroid 2-related factor 2 /antioxidant response element signaling.Conclusion: Collectively, these findings provide a new insight on the role of ES-GNs in treating chronic neuroinflammation-induced neurodegenerative diseases.Keywords: gold nanoparticle, Ephedra sinica Stapf, microglia, neuroinflammation